Research uptake - what is it, why bother and are you good at it? - Marry, Anna.; Rajeesh, Sangeetha. (Tufts University. Tisch Library., 2017)
This session provides an introduction to research uptake: definitions, approaches, tools and techniques. Attendees were introduced to the LANSA self-assessment tool, which will allow them to assess their organization's or team's research uptake capacity.